"Creative Non-compliance": Complying with the "Spirit of the Law" Not the "Letter of the Law" under the Covid-19 Lockdown Restrictions. Issue 1 (2nd January 2023) - Meers, Jed; Halliday, Simon; Tomlinson, Joe
ABSTRACT: This paper identifies a form of non-compliance with COVID-19 lockdown restrictions in the UK: "creative non-compliance". Here, individuals justify breaking restrictions as meeting the "spirit of the law" if not the "letter of the law". Drawing on interview and focus group data collected between April and August 2020, we outline this concept of "creative non-compliance, " detailing how: (i) our participants undertook a purposive construction of rules, (ii) balanced their behavior against these aims, and (iii) how Government messaging informed these rationalizations. We conclude by outlining the implications of our "creative non-compliance" theory both for studies of compliance and rationalizations for deviant behavior under the COVID-19 restrictions.